The Effect of Green Investment and Corporate Social Responsibility On The Financial Performance of Mining Companies Listed on The Indonesia Stock Exchange for the 2020-2023 - Joni Kurniawan Gea; Dimita Hemalli Premasari Purba; Yosephine Natalitha Sembiring; Arthur Simanjuntak (Program Studi Akuntansi Universitas Simalungun, 2026)
The purpose of this study is to analyze the effect of Green Investment and Corporate Social Responsibility factors on Company Value. The formulation of the research problem is whether Green Investment and Corporate Social Responsibility affect Financial Performance. The sample used was 12 companies. The data used in this study were obtained from the annual financial reports of Mining Sector companies in 2020-2023. The population of companies in this study consisted of 40 Mining sectors listed on the Indonesia Stock Exchange (IDX) in 2020-2023. A total of 10 samples were used in this study with sample selection using the purposive sampling method. The data analysis used was descriptive statistics, classical assumption tests and hypothesis testing with the regression method using SPSS 26. This study used a quantitative descriptive research design. The analysis technique used was multiple linear regression. The results showed that Green Investment has a positive effect on Financial Performance, Corporate Social Responsibility has no an effect on Financial Performance